Hydrotalcite-supported Pd–Au nanocatalysts for Ullmann homocoupling reactions at low temperature. (13th February 2017) - Wang, Jiang; Xu, Aiju; Jia, Meilin; Bai, Sagala; Cheng, Xiaodan; Zhaorigetu, Bao
Abstract : Ullmann homocoupling reactions of aryl bromides or chlorides at 40 °C were realized by using Pd–Au x nanocatalysts supported on Mg3 –Al hydrotalcite. Abstract : Hydrotalcite-supported Pd–Au nanocatalysts were found to be efficient heterogeneous catalysts for Ullmann homocoupling reactions of aryl bromides or chlorides at 25 or 40 °C, which could be due to the ensemble effect and increased electron density of Pd sites on Pd–Au nanoparticles, and the assistant role of the hydrotalcite for the reversion of the catalytic active center, Pd(0).